Automatized failure analysis of tungsten coated TSVs via scanning acoustic microscopy. (September 2016) - Grünwald, E.; Rosc, J.; Hammer, R.; Czurratis, P.; Koch, M.; Kraft, J.; Schrank, F.; Brunner, R.
Abstract: In 3D integrated microelectronics, the failure analysis of through silicon vias (TSVs) represents a highly demanding task. In this study, defects in tungsten coated TSVs were analysed using scanning acoustic microscopy (SAM). Here, the focus lay on the realization of an automatized failure detection method towards rapid learning. We showed that by using a transducer of 100 MHz center frequency, established with an acoustical objective (AO), it is possible to detect defects within the TSVs. In order to interpret our analysis, we performed acoustic wave propagation simulations based on the elastodynamic finite integration technique (EFIT). In addition, high resolution X-ray computed tomography (XCT) was performed which corroborated the SAM analysis. In order to go towards automatized defect detection, firstly the commercially available software "WinSAM8" was enhanced to perform scans at defined working distances automatically. Secondly, a pattern recognition algorithm was successfully applied using "Python" to the SAM scans in order to distinguish damaged TSVs from defect-free TSVs. Besides the potential for automatized failure detection in TSVs, the SAM approach exhibits the advantages of fast and non-destructive failure detection, without the need for special preparation of the sample. Highlights: The paper Automatized Failure Analysis of Tungsten Coated TSVs via Scanning Acoustic Microscopy highlights the analysis of 3D integrated microelectronics. In detail TSV structure are analyzed by using scanning acoustic microscopy, computed tomography and ultrasound simulations. It is shown in the article that acoustic microscopy presents a highly valuable tool for the characterization of TSV structures.